The Implementation of Semester Credit System-Based Economic Learning in The 2013 Curriculum Application of Senior High School - Setyawan, Abigail Puteri; Soesilo, Yohanes Hadi (Unversitas Negeri Malang, 2019)
This paper intends to describe and discuss the implementation of semester credit system-based learning in Economics subject of senior high school. This research used qualitative field research approach to identify the implementation of semester credit system-based learning in SMAN 2 Mojokerto. The data collection was obtained through interviews, field observation, and documentation. Based on the data obtained, the implementation of semester credit system-based learning has been conducted well. However, the researchers discovered that there were some obstacles such as studentsâ€™ lack of motivation, enthusiasm, and responsibility. Thus, it is important for teachers and school counsellors to direct and guide students during the learning process.Â